2017
DOI: 10.1242/jeb.164020
|View full text |Cite
|
Sign up to set email alerts
|

Multimodalin situdatalogging quantifies inter-individual variation in thermal experience and persistent origin effects on gaping behavior among intertidal mussels (Mytilus californianus)

Abstract: In complex habitats, environmental variation over small spatial scales can equal or exceed larger-scale gradients. This small-scale variation may allow motile organisms to mitigate stressful conditions by choosing benign microhabitats, whereas sessile organisms may rely on other behaviors to cope with environmental stresses in these variable environments. We developed a monitoring system to track body temperature, valve gaping behavior and posture of individual mussels () in field conditions in the rocky inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 73 publications
2
63
2
Order By: Relevance
“…The low cost and long life of the sensor and data logger package permit their usage in field settings where tide cycles and wave action might make other forms of long‐term observation such as human observers or cameras impractical. More generally, the types of sensor packages described here are providing new insights into bivalve feeding behavior (Riisgård, Lassen, & Kittner, ), growth (Ballesta‐Artero, Witbaard, Carroll, & van der Meer, ), responses to water quality (Sow, Durrieu, Briollais, Ciret, & Massabuau, ; Tran, Ciret, Ciutat, Durrieu, & Massabuau, ), and can allow researchers to better link the organism's interaction with the environment to its physiological status (Dowd & Somero, ; Gleason et al., ; Miller & Dowd, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The low cost and long life of the sensor and data logger package permit their usage in field settings where tide cycles and wave action might make other forms of long‐term observation such as human observers or cameras impractical. More generally, the types of sensor packages described here are providing new insights into bivalve feeding behavior (Riisgård, Lassen, & Kittner, ), growth (Ballesta‐Artero, Witbaard, Carroll, & van der Meer, ), responses to water quality (Sow, Durrieu, Briollais, Ciret, & Massabuau, ; Tran, Ciret, Ciutat, Durrieu, & Massabuau, ), and can allow researchers to better link the organism's interaction with the environment to its physiological status (Dowd & Somero, ; Gleason et al., ; Miller & Dowd, ).…”
Section: Discussionmentioning
confidence: 99%
“…The instrumentation and datalogging systems used for the mussels in this experiment are described in Miller and Dowd (). Briefly, we created an artificial mussel bed comprising 12 instrumented live mussels and several dozen additional live mussels (adult body size 40–70 mm shell length, harvested from the mid‐intertidal zone at HMS) on a 45 × 30 cm acrylic plastic plate (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results suggested no significant difference in animal temperature. Miller and Dowd (2017) also found that live M. californianus mussels in the intertidal that experienced high body temperatures during low tide (>25 • C) generally kept their shells closed more often than cooler mussels meaning this species likely does not utilize cooling through evaporation to control body temperature during hot conditions. Nicastro et al (2012) showed that individual mussels did not apparently cool as a result of gaping, but suggested that entire beds of mussels, acting in concert, could lead to overall cooling.…”
Section: Accounting For Behavioral Thermoregulationmentioning
confidence: 93%